Mechanism of Wheat's Drought Tolerance: A Review (Journal of Asian Development Studies, 2023)
The majority of crops cultivated in tropical and subtropical regions across the world face significant risks due to climate change. Drought is one of the most critical environmental factors that might reduce agricultural productivity and yield. When crops are subjected to drought stress, they exhibit a variety of reactions on several levels, including the morphological, physiological, biochemical, and molecular levels. Polygenes regulate a sophisticated trait,drought tolerance, and a wide variety of environmental factors modulate the expression of these polygenes. In addition, drought stress affects plant protein changes, hormone composition, root depth and extension, osmotic adjustment, antioxidant generation, opening and closing of stomata, cuticle thickness, inhibition of photosynthesis, decreased transpiration, and growth may affect inhibition and chlorophyll content. In addition to various osmotic changes in their organs. Plants respond to drought by activating defense mechanisms, which cause a decrease in grain yield, changes in photosynthetic parameters, and an increase in specialized metabolic chemicals. This review article investigates water restriction and its effects on wheat's morphological, physiological, biochemical, and molecular responses concerning potential damage caused by drought stress.